Review of design and challenges of DC SSPC in more electric aircraft - Molligoda, Devinda A. (2021)
Solid State Power Controller (SSPC) is gaining popularity, replacing mechanical switches and circuit breakers, in niche markets like electrical power distribution systems of the more electric aircraft. Significant amount of research is being conducted to develop high power SSPCs to cater the dynamic, distributed load management. The 28V SSPCs are widely used for protection and control of the secondary distribution system. Although there are high current SSPCs for low bus voltages, the 270V SSPCs are not mature and high current 270V SSPCs are not available in the market or having limited capability, which would be used in the primary power distribution system of the aircraft. This paper presents the market availability, design challenges the design engineer should be aware of and various approaches adopted to design and develop a high current 270V DC SSPC for more electric aircraft system, its key features which may not have been available in the traditional switches and future trends.